On single-crystal neutron-diffraction in DACs: quantitative structure refinement of light elements on SNAP and TOPAZ. Issue 3 (2nd July 2020) - Massani, B.; Loveday, J. S.; Molaison, J. J.; dos Santos, A. M.; Wang, X. P.; Daemen, L. L.; Haberl, B.; Boehler, R.; Guthrie, M.
ABSTRACT: Quantitative single crystal neutron-diffraction in diamond anvil cells has so far been limited by the neutron flux available at the various neutron sources. As a result, highly precise measurements of the exact position of light elements have not been possible preventing, for example, structural studies of hydrogen and hydrogen bonds under pressure. Here we report experiments carried out on SNAP at the Spallation Neutron Source (ORNL, TN, USA) to explore the possibility and current limits of such studies. Furthermore, we benchmarked the obtained data quality with reference experiments carried out on TOPAZ, a dedicated single-crystal instrument. We show that measuring single-crystal diffraction intensities on SNAP is possible to such a precision that we are able to resolve the hydrogen bonds in potassium dideuterium phosphate (DKDP) as well as in ice VI.